The Influence of Tax Revenue and Government Expenditure on Infrastructure Development - Viktor Andrio Sunardi; Aloisius Hama (Journal of Creative Power and Ambition (JCPA), 2026)
The key to the success of this decentralization policy is highly dependent on the independence of the regional budget in order to finance various strategic agendas independently in accordance with the mandate of the latest regulations. Accelerating the development of public facilities is a fundamental pillar for economic sustainability in West Manggarai Regency, especially as an international tourist destination. This research aims to empirically dissect the extent to which the variables of regional tax revenue and public expenditure allocation play a role in constructing the face of regional infrastructure. By adopting a quantitative framework based on secondary data for the 2018–2024 period, the results of statistical evaluation confirm that the synergy between the optimization of tax fund mobilization and the effectiveness of simultaneous regional expenditure management is the main determinant in expanding the reach and quality of physical infrastructure. These findings confirm that fiscal independence and budget allocation precision are key in spurring the transformation of public facilities that are in line with the vision of regional development.